LEGALITAS DAN TANGGUNG JAWAB KOREA UTARA ATAS UJI COBA SENJATA NUKLIRNYA - Dwiky Chandra; Teddy Nurcahyawan (Jurnal Hukum Adigama, 2018)
The legality of nuclear development and testing has been controversial among international community. North Korea, on 3 September 2017, conducted a nuclear testing that exploded in North Pacific Ocean by crossing the air of Hokkaido City, Japan. The nuclear testing has led to international complaints. As a state that has withdrawn from the Non-Proliferation Treaty since 2003, North Korea is not bound by the treaty law. However, it is argued that Article 2(4) of United Nations Charter prohibits nuclear development and nuclear testing. The legal issues arisen are whether or not the nuclear testing of North Korea is legal and responsible for the nuclear testing. The research applies normative method research. This research reveals that the nuclear testing conducted by North Korea is not legal and shall be liable for internationally wrongful act as it is inconsistent with international law.